Fascisme et science-fiction - Aaron Santesso (ReS Futurae)
A great deal of recent criticism has made the case that sf is “naturally” liberal and progressive. This essay will argue that such claims underestimate the diversity of the genre, overlooking the ways in which certain foundational tropes and narrative structures (evident most clearly in pulp-era sf) invite plots and figures aligned more closely with fascism than with progressive thought. For some critics, the anti- progressive politics of many pulp-era works is an unfortunate historical quirk, long since transcended and forgotten ; this essay argues, on the other hand, that a kind of latent pulp-era fascism survives even in much ostensibly progressive contemporary sf. Tracing the afterlife of fascist tropes and themes complicates a host of critical claims about the ideological leanings of the genre.